TA’ZIR SANTRI IN THE PERSPECTIVE OF LEGAL AND MORAL DIALECTICS - Fahrurrosin,; Hidayat, Ihsan; Abdel Rahman Houssein, Abdel Hakim; Alimuddin , Khasan (JIL : Journal of Indonesian Law, 2024)
This research analyzes implementation of ta’zir at Salafiyah Islamic Boarding School Grogol, Salatiga, as a step toward harmonizing law and morals. Ta’zir is often perceived negatively being contradictory to legal morality. However, within context of Islamic boarding schools, ta’zir is an integral part of educational traditions rooted in local cultural values. This research employs a qualitative approach, utilizing interviews and direct observations to gather primary data from administrators and santri. The findings reveal that ta’zir at Salafiyah Islamic boarding school is a product of collective agreement, reflecting religious morality and legal culture of Islamic boarding school. Punishments such as Qur'an recitation or material contributions are designed to educate santri, foster accountability, and create social harmony. In conclusion, ta’zir is not merely a disciplinary mechanism but also a character-building tool aligned with both law and morality.